Growth performance of tilapia using sago (metroxylon sagu) as die - Juat, Florida Easter anak (Universiti Malaysia Sarawak, 2011)
This experiment was conducted to test the formulated diets enhanced using different percentage of Metroxylon sagu (M.sagu) in order to observe the growth performance of Oreochromis mossambicus (O. mossambicus). Main objectives of this study were to determine the best percentage quantity of M. sagu for growth performance of O.mossambicus and to identify the suitablity of diets formulated using M. sagu. Effects of formulated diets enhanced with M. sagu were evaluated for a period of 9 weeks. Fifteen individual fry were stock in each treatment and were feed daily with 30%, 50%, 70% of M.sagu and commercial diets which defined as Treatment A, Treatment B, Treatment C, and Treatment D respectively. The length and weight of ten individual fry of each treatment was measured weekly while water quality parameter such as pH and Temperature were measured every two week. There was no significance different of mean weight and mean total length for all treatment at early experiment. However, there was significance different among treatment at end of experiment. Treatment D has shown the highest mean weight, mean total length and also specific growth rate. Treatment C had shown the highest survival rate among treatment. Further study on diet formulated enhance using plant based protein was recommended.